PRIMARY COURSE DROP OUT IN THE MUNICIPALITY OF DJOUGOU : DESCRIPTIVE STUDY - BIGA BOUKARY, Alassane; AHONNON, Adolphe; EDOH, KOFFI PIERROT; KASSOUMOU, Arouna (My University, 2018)
The issue of de-schooling has become the leitmotiv of all debates on education as a development factor. Indeed, like many developing countries, Benin is affected by the phenomenon; especially in the northern part of its territory. At the analysis, the causes of the dropout are multiple. However, they can be categorized into three: social causes; the causes of religion and then the causes of economic order. The present research work entitled "De-schooling in the municipality of Djougou: descriptive study" is carried out with the aim of describing the phenomenon of de-schooling from the case of the commune of Djougou. The research methodology used in this study is a questionnaire, interview and observation survey. Fieldwork allowed for data collection, processing and analysis of results. Thus, the results of this research made it possible to conclude, on the one hand, that the teaching/learning conditions favor the de-schooling in the commune of Djougou, and on the other hand that the phenomenon of de-schooling is underpinned by the social, economic and religious heaviness.
Keywords: Drop out - primary school – municipality - teaching / learning